How to fight myasthenia gravis fatigue - Farzanegan, Z (Iran University of Medical Sciences, 1995)
When stretcher came to unit and I was put in my bed, nursing personnel of surgical ward said to me hello. I had seen their face from yesterday night when they were transferring patients from emergency ward to this unit.  In that time, I had the role of emergency ward assistant manager. Today, I am a weak patient that even is unable for smallest movement. Cause of my admission to hospital is muscle paralysis that has engendered by diphenhydramin (benadryl) consumption. I had eaten this drug for relief of allergic reaction related to scan's contrast substance use. My disease diagnosis was myasthenia gravis. All of these problems started four years ago and short time after my twin girls born. Every time I embraced my children, my arms most weakened and I had fatigue feeling.